Trial of Integrated Biotechnical Approach in Biological Reclamation of Coal Mine Spoil Dumps in South-Eastern Coalfields Limited (S.E.C.L.), Bilaspur (Madhya Pradesh) - Kumar, U.; Jena, S. C. (Indian Forester, 1996)
After physical reclamation of coal mine spoil dumps of SECL, Bilaspur (M.P.) a trial on biological reclamation through Integrated Biotechnical Approach was conducted. The height of overburden dumps was reduced and the top was flattened and given the shape of a saucer with the help of dozers. Saplings were planted in pits of 0.6 m × 0.6 m × O.6m size and fined with 4 parts of overburden soil, 1 part top soil collected from nearby areas and 15 kg of farm yard manure. The leguminous plants were inoculated with specialised cultures of Mycorrhizae-Rhizobium inoculum while Mycorrhizae-Azatobacter inoculum was used for non-leguminous plant species. In between the rows of trees inoculated Pennisitum pedicellatum and Heteropogon contorlus grasses mixed with Stylosanthus hemala were sown on beds of 1.0 m × 1.5m size. All these together have helped in controlling soil erosion, improving physical and chemical qualities of soil, increasing plant heights by 2.4 to 5.1 times more than normal growth of controls and achieving a plant survival percentage of 92%.